Media coverage of climate change information by the Tanzania Guardian and Daily News in 2015. (September 2019) - Elia, Emmanuel
The study examined the reportage of information on climate change in the Guardian and the Daily News, two leading broadsheet newspapers in Tanzania. Data were collected and analysed using the informetrics method. Content analysis was used to delineate themes. Quantitative data generated was analysed using Microsoft Office Excel Software 2007 to generate graphs and charts. In all, 338 articles from 728 newspaper issues from January to December 2015 were collected and analysed. Key findings indicate that climate change impacts and adaptation, climate change conferences and policy, politics and development were themes mostly covered in the two newspapers under review. Findings also indicate an increased coverage of international and local climate change news. The study concludes that the access of journalists to relevant and reliable Internet resources influenced the climate change information appearing in the two newspapers. Thus, the study recommends for climate scientists and policy-makers to train journalists on proper analysis and reporting of climate related information. Moreover, the study suggests establishing a communication policy framework designed to enhance journalists' and media owners' access to and effective dissemination of climate change information.